A new zeolite formed from interlayer expansion of the precursor COK-5 - Bian, Chaoqun; Wu, Qinming; Zhang, Jian; Chen, Fang; Pan, Shuxiang; Wang, Liang; Meng, Xiangju; Müller, Ulrich; Feyen, Mathias; Yilmaz, Bilge; Gies, Hermann; Zhang, Weiping; et al. (Microporous and Mesoporous Materials, 2015)
The layered silicate COK-5 has been used for an interlayer expansion reaction with dichlorodimethylsilane (DCDMS) at 180 °C to interconnect neighboring layers, yielding a new and crystalline microporous framework. The samples containing the methyl functional groups in the as-made form and having OH groups in the calcined form were designed as COE-5 and calcined COE-5. These samples were characterized with X-ray diffraction (XRD), N2 sorption isotherms, inductively coupled plasma optical emission spectrometry (ICP-OES), infrared spectroscopy (IR), high-resolution transmission electron micrograph (HRTEM), thermogravimetry-differential thermal analysis (TG-DTA), and 29Si and 13C solid-state magic-angle spinning nuclear magnetic resonance (MAS NMR), as well as the contact angle techniques. XRD patterns and HRTEM images suggest that the sample interlayer spacing has been expanded by nearly 0.5 Å. The N2 sorption isotherms of the materials show the BET surface areas are 165 m2/g for COE-5 and 340 m2/g for calcined COE-5. 29Si and 13C MAS NMR as well as IR spectroscopy confirm the insertion of the linker group -Si(CH3)2- connecting neighboring layers. Interestingly, calcined COE-5 shows enhanced catalytic performance in the acetalisation of glycerol with acetone to produce solketal, compared with COK-5. [Display omitted] •COE-5 zeolite has synthesized via an interlayer expansion of COK-5 layers.•The COE-5 interlayer spacing has been expanded to nearly 0.5 Å.•The sample wettability can be adjusted by controlling the methyl and silanol groups.•The COE-6 zeolite is very active in catalytic acetalisation of glycerol to solketal.